The politics of regicide in England, 1760-1850 : troublesome subjects - Poole, Steve, 1957- (Manchester University Press, 2018)
This lively and accessible book reappraises the often complex relationship between British monarchs and some of their more troublesome subjects in the 'age of revolutions'. By exposing a rationale behind the efforts of the mad and the politically disaffected to intrude upon, assault or pester kings and queens from George III to Victoria, the author casts new light upon the contested languages of constitutionalism, contract theory and the rights of petition. The Hanoverian dynasty sought security from republicanism during the 1790s by reinventing itself as an affable, domestic, flexible and solicitous institution. But majesty and approachability were to prove uneasy bedfellows, and popular frustrations over unanswered petitions could provoke serious personal moments of crisis. In its detailed reconstruction of the mentalities of such unsuccessful and forgotten Royal 'assassins' as Margaret Nicholson, James Hadfield and Dennis Collins, this unique and pioneering study of monarchical history from below will interest the specialist and general reader alike, and provoke fresh controversy over the viability of monarchies in the modern world.